(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
In recent decades, there has been a significant increase in the incidence of fungal diseases. Certain fungal diseases cause cutaneous lesions and in the usual treatment, generally administred orally, the drug reaches the site of action with difficulty and its concentration is too low. An approach much explored in recent years is the development of nanotechnology-based drug delivery systems, and microemulsions (ME) and liquid crystals (LC) are promising. ME and LC were developed with oleic acid or copaiba oil as the oil phase, propoxyl (5OP) ethoxyl (20 OE) cetyl alcohol as surfactant and water. An analytical method to assess the incorporation of fluconazole (FLU) in the systems under study was validated according to guidelines of the International Conference on Harmonization (ICH) guidelines and the Brazilian Food, Drug and Sanitation Agency (ANVISA). The method was conducted on a C18-RP column (250 × 4.6 mm i.d.), maintained at room temperature. The mobile phase consisted of acetonitrile and water (50:50, v/v), run at a flow rate of 1.0mL/min and using ultraviolet detection at 210nm. The chromatographic separation was obtained with a retention time of 6.3min, and was linear in the range of 20-400 µg/mL (r2=0.9999). The specificity showed no interference of the excipients. The accuracy was 100.76%. The limits of detection and quantitation were 0.057 and 0.172 µg.mL-1, respectively. Moreover, method validation demonstrated satisfactory results for precision and robustness. The proposed method was applied for the analysis of the incorporation of FLU in ME and LC, contributing to improve the quality control and to assure the therapeutic efficacy.